Complexidade dos sintagmas nominais do inglês: um estudo comparativo de corpora de aprendizes brasileiros e falantes nativos de inglês - Vanessa Cristina Oliveira Wright (2017)
This study describes the complexity of noun phrases produced by Brazilian learners, morespecifically, the noun modifiers. The concepts used in this research are based ondescriptive grammars of English which have a functionalist bias, bringing examples oflanguage in use, or which are based on reference corpora. Three corpora were used inthis work: BR-ICLE (International Corpus of Learner English, study corpus), LOCNESS(Louvian Corpus of Native English Essays, comparative corpus) and BAWE (BritishAcademic Written English, reference corpus), which represent the linguistic production ofBrazilian apprentices, the linguistic production of American and British English nativespeakers, and the linguistic production of British university students from various fields ofstudy, respectively. I propose a measurement for noun phrase complexity, and analyzedata in native and learner corpus with this measurement. In addition, WordSmith Toolscorpus linguistics tool was used to conduct the research. This research was carried outbased on the hypothesis that learners noun phrases are structured differently from nativespeakers, and that they tend to be less complex. This lower complexity occurred in thedensity of the noun phrase produced by the learner. The learners writing wascharacterized by being strongly pre-modified, to the detriment of post-modification. Premodificationoccurred more often as adjectives, and it occurred less frequently as nouns.In addition, learners used fewer non-finite clauses and prepositional phrases as postmodifiers,compared to natives.